Assessing the fracture hazard of railroad rolling stock wheel flange based on bending stresses and contact fatigue - Sapronova, Svitlana; Vorobiov, Oleksandr; Klymash, Andriy (Eastern-European Journal of Enterprise Technologies, 2026)
This study investigates the stressed-strained state of a wheel flange in railroad rolling stock under the action of lateral forces of the wheel-rail interaction and the evolution of contact-fatigue damage. The task addressed relates to the lack of a comprehensive assessment of the risk of wheel flange failure, which would simultaneously take into account bending stresses, contact fatigue, and changes in the thickness of the flange due to operational wear. The wheel flange is proposed as a bending element loaded by the lateral force of the wheel-rail interaction. An analytical dependence has been derived for determining bending stresses depending on the thickness of the flange and the magnitude of the lateral force. A hazard index is proposed, constructed by normalizing equivalent contact stresses relative to the contact endurance limit of the wheel material. Based on the combination of the contact index and the fatigue safety factor, a combined criterion for assessing the risk of flange failure has been devised. A feature of the results is the established analytical dependence between the thickness of the flange and the fatigue stresses of bending. It was found that reducing the thickness of the flange from 30 to 22 mm leads to an increase in fatigue stresses by almost 1.9 times. A map of the risk of fracture in the coordinates "flange thickness-lateral force" was constructed, which makes it possible to determine the areas of safe and dangerous operation. The scope of practical implementation of the results is railroad transport. A condition for applying the findings is to assess the technical condition and predict the resource of rolling stock wheel flanges under the action of lateral loads in the flange contact. This study could contribute to increasing the efficiency of the maintenance system of wheelsets for railroad transportation